Possible Variations of Thyroid Gland: A Detailed Cadaveric Study - Movva Venkata Vinaya Kumar; Reshma Mohammad; Sreelatha S (International Journal of Anatomy Radiology and Surgery, 2018)
Introduction: The knowledge regarding the identification of anatomical variations of thyroid gland is very important in formulating planned surgical approaches to the thyroid gland and in alerting the surgeons to prevent accidental injuries to the vital anatomical structures in this area. Aim: To find out the possible anatomical variations and morphometric parameters of the entire thyroid gland. Materials and Methods: A total of 60 thyroid glands were studied in the cadavers by routine neck dissection method. The morphological variations, arterial supply variations and the morphometric parameters of length, breadth, and thickness were observed. Results: Out of 60 thyroid glands we observed one thyrotrachealis biceps muscle. Isthmus was absent in 5 (8.3%) of cases, pyramidal lobe was present in 8 (13.3%) of cases, levator glandulae thyroidae was in 3 (5%) of cases , the left STA from LCC in 3 (5%) of cases, left STA bifurcation level in 2 (3.3%) of cases, right STA from right ECA lateral side in 1 (1.6%) of cases, arteria thyroidae ima from arch of aorta was in 1 (1.6%) of cases, the minimum and maximum length of the right lobe was 1.9 cm, 6.9 cm and for the left lobe was 2.1 cm, 5.8 cm, the minimum and maximum breadth of the right lobe was 0.94 cm, 3.72 cm and for the left lobe was 1.2 cm, 3.5 cm, the minimum and maximum thickness of the right lobe was 0.87cm,2.9cm and for the left lobe was 0.7 cm, 2.5 cm, the average weight of the thyroid gland was 14.4 gm. Conclusion: Thyroid gland in a cadaver caught our attention as it had multiple variations. The implications of such variations are relevant for academic and clinical purposes.